Application and Modification of the Integrative Model for Environmental Health. Issue 2 (7th September 2012) - Polivka, Barbara J.; Chaudry, Rosemary; Crawford, J. Mac; Wilson, Robyn; Galos, Dylan
Abstract The Integrative Model for Environmental Health (IMEH) has guided research, literature reviews, and practice initiatives since 2002. This article presents the Modified IMEH that was developed based on using the IMEH as a guiding conceptual framework in a community‐based participatory research environmental health project. Concepts from the Model of Risk Information Seeking and Processing as well as emergent themes from the data analysis were instrumental in this process. The Modified IMEH alters the structure of the IMEH in that the Vulnerability and Epistemological Domains are more prominent and feedback between domains is included.